Uranium Dust Cloud Combustion: Burning Characteristics and Absorption Spectroscopy Measurements. (16th November 2022) - Weerakkody, Emily N.; Read, Brian A.; Clemenson, Michael D.; Glumac, Nick G.
Abstract : This study characterized uranium metal dust cloud combustion using absorption spectroscopy, imaging, and broadband emission measurements. Other metals were similarly combusted to establish correlations between results from this study and those found in the literature. It was determined that the burn temperature of uranium was limited to the volatilization temperature of uranium dioxide. Combustion behavior was similar to that of other refractory metals in terms of burn time and the observation of exploding particle behavior.